Growth status and the risk of contracting primary tuberculosis. Issue 5 (May 1983) - Rona, R J; Chinn, S; Marshall, B S; Eames, M
Abstract : A case of open tuberculous infection in a member of staff at a primary school resulted in an outbreak in which nearly a quarter of the children in the school contracted a primary infection. The growth status of these children was compared with that in the non-infected children before the outbreak and on two occasions after the outbreak. The children with tuberculous infection were taller and fatter than the controls before and after the outbreak but differences were not always statistically significant. Among children with a good nutritional status the thin and small child is at no greater risk of contracting primary tuberculous infection than other children.